DESKRIPSI KESALAHAN SISWA BERDASARKAN KLASIFIKASI WATSON DALAM MENYELESAIKAN SOAL-SOAL SUHU DAN KALOR - Yulianda, Putri; Sahala, Stepanus; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research has purpose to describe student’s error based on Watson’s Classification in solving temperature and heat problems. Watson’s Classification has eight category of errors are inappropriate data (id), inappropriate procedure (ip), omitted data (od), omitted conclution (oc), response level conflict (rlc), undered manipulation, (um) skill hierarchy problem (shp) and beside those seven errors (ao). This research is done to 53 students of  Grade X in SMA Negeri 3 Pontianak.  Collector instrument of data is 10 essay problems about temperature and heat problems. In this research using Watson’s Classification because this classification has compelete category of error. With this classification we can see error of students in solving problems. Percentage of error is done by 53 students is 22,6% id, 10,1% ip, 0,35% od, 15,6% oc, 9,7% rlc, 0% um, 3,1% shp and 38,5% ao. Beside that, in this research there is percenatge of 27,92 % sudents answer questions correctly, 37,73 % student answer questions incorrectly and 34,34 % students don’t answer questions.Keywords: Description, student’s error in solving temperature and heat problems,      Watson’s classification